PROFITABILITAS TERHADAP FINANCIAL DISTRESS DIMODERASI STRUKTUR MODAL - Baiq Vica Artamevia; Nanik Wahyuni (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to determine the effect of profitability on financial distress moderation of capital structure is carried out to be a research renewal. profitability is projected by ROA and ROE, while the capital structure is projected by DER. The research uses financial reports and annual reports to complete the research data. The population and sample used are coal sector companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 2018 to 2020. Data analysis uses SmartPls3 software by utilizing the Path Coefficient test to test hypothesis. The results show that profitability has no effect on financial distress in brick-and-mortar companies and the capital structure is not able to influence the relationship between profitability and financial distress in coal sector companies.